"...But the One who Prophesies, Builds the Church": Nation Building and Transformation Discourse as true prophecy: The case of Zimbabwean Pentecostal women - Biri, Kudzai; Togarasei, Lovemore (Prophets, Profits, and the Bible in Zimbabwe: Festschrift for Aynos Masotcha Moyo, 2013)
This chapter celebrates the achievements of Pentecostal women in Zimbabwe in the discourse of nation building and transformation during the crisis years of the late 1990s to about 2013. During this period, Pentecostal women rose and gained space and visibility through their interdenominational fellowships. The chapter highlights the role that the women have played in addressing challenges brought by the crisis. Using the New Testament, and especially the Pauline, understanding of prophecy, the chapter then argues that Pentecostal women’s discourses of nation building and transformation were indeed prophetic. It compares and contrasts women’s ‘prophecies’ with the prophetic acts of some men whose practices put the office of the prophet into disrepute.
free